(3GdgOGjI TQM GdHOGjIs - (3Ydj Hf CHj HcQ Hf YHO GdLdjd GdaQZGfj GdeQZjfGfj, CHh GdMSf HQgGf GdOjf,J (B593 (3g` s ((3eMeO GdedbH HaNQ GdOjf s)
(3ChdgG (B:s
(3jHOC HcJGH GdUQa s
(3BNQgG (B:s
(3hGddg Gdehab ddUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B45s
Keywords: (3Gdabg GdMfajs